"A Web of Tension": The 1967 Protests in New Brunswick, New Jersey. (January 2014) - Rasmussen, Chris
Historians have recently examined the Civil Rights movement in the North and the links between its nonviolent tactics and the violent protest that erupted in many Northern cities in the 1960s. In 1967, unrest arose in Newark, Detroit, and many other cities. New Brunswick, only twenty-five miles from Newark, experienced protests on two successive nights in July 1967, but averted loss of life and massive destruction of property. The report of the Kerner Commission credited New Brunswick Mayor Patricia Sheehan's conciliatory approach with averting violence. An examination of the Kerner Commission's papers suggests a more complex dynamic, one that confirms the mayor's key role, but also reveals that antipoverty workers, black leaders, and the protestors themselves played significant roles in averting violence. The protestors strategically put pressure on the mayor, and then relented when she promised to improve conditions for the city's poor and black residents.